La préparation et le passage du recensement du Soudan 2008 - Eric Denis; Julien Dupuy (EchoGéo)
The Fith population census enumeration operations have just been achieved. They have to meet the 38 millions inhabitants of the largest countries of Africa with a unique questionnaire shared by two statistical institutions, one in the North and a second for the South. The census is a milestone of the peace agreement of 2005 that put an end to the civil war between the Nord and the South. The census results are extremely waited as they will determine the petrol dividend sharing, the parlement election of 2009 and the independence referendum of 2011. So much stakes, identity and ressources access, control and redistribution conflicts at all scales and in every sudanese margin are pushing the census to catalyse and finally reveal the tragical limits of an ethnocratic governance.